Interdisciplinary neurovascular networks in Germany: update 2025 - Tobias A. Wagner-Altendorf; Konrad Sieb; Ansgar Berlis; Arnd Dörfler; Dorothee Mielke; Christoph Groden; Erdem Güresir; Gerhard F. Hamann; Olav Jansen; Jürgen Meixensberger; Oliver Müller; Darius G. Nabavi; et al. (Neurological Research and Practice)
Abstract Background Neurovascular networks (NVNs) in Germany are supra-regional care structures for patients with neurovascular diseases. Each NVN consists of a tertiary care center serving as the coordinating center—in some cases, two or three coordinating centers—and at least three partner hospitals. Since 2018, 19 neurovascular networks (NVNs) have been audited and certified. NVNs play a crucial role in stroke care in Germany, as first described and quantified in 2020. Methods The present article provides an update on interdisciplinary NVNs in Germany and outlines recent developments in neurovascular patient care. Audit reports from 19 NVNs, certified between 2021 and 2024, were analyzed, and compared to previously reported data from 2017 to 2019. Additionally, structural and quality-related parameters for coordinating centers and partner hospitals were compared. Results The number of NVNs increased from 15 to 19, with approximately 120,000 from an estimated 262,000 neurovascular patients in Germany now treated annually in certified NVN hospitals. In particular, annual thrombectomy rates at coordinating centers have increased over-proportionally (> 4400, as compared to previously < 2500), and surgical treatments for intracerebral hemorrhages have also increased. Process times—door-to-needle and door-to-groin times—remained stable or exhibited slight increases. Substantial variability was observed among NVN partner hospitals regarding procedural volumes. Conclusions The treatment of patients with neurovascular diseases in Germany has expanded considerably within certified NVN hospitals in recent years. The NVNs ensure comprehensive, high-quality stroke care nationwide.